Development of a Stability Indicating Method for Simultaneous Analysis of Five Water-Soluble Vitamins by Liquid Chromatography - Yessaad Mouloud; Bernard Lise; Bourdeaux Daniel; Chennell Philip; Sautou Valérie (De Gruyter, 2018)
Water-soluble vitamins are often included simultaneously in pharmaceutical formulations as food complements or in parenteral nutrition mixtures. Given their sensitivity to heat, light or pH variations, it is important to study their stability using validated stability indicating methods. We thus aimed to validate a liquid chromatography (LC) stability-indicating method for the simultaneous quantification of 5 water-soluble vitamins.